Hydrogen- and halogen-bond driven co-crystallizations: from fundamental supramolecular chemistry to practical materials science - Widanalage Dona, Tharanga Kumudini Wijethunga (Kansas State University, 2015)
A series of co-crystallizations between four biimidazole based compounds with nine symmetric aliphatic di-acids and fifteen perfluorinated halogen-bond donors were carried out to determine if a MEPS based ranking can be used to effectively assign selectivity in hydrogen- and halogen-bond interactions. The results suggested that a simple electrostatic view provides a reliable tool for successfully implementing the practical co-crystal synthesis with desired connectivity. MEPS based selectivity guidelines for halogen-bond interactions were explored in co-crystallizations between twelve asymmetric ditopic acceptors and nine halogen-bond donors. If the difference between the two acceptor sites is below 35 kJ/mol, no selectivity was observed; above 65 kJ/mol halogen bond selectivity dominates and mid ΔE range was recognized as the grey area where predictions cannot be made. To examine competition between hydrogen and halogen bonds, five heteroaryl-2-imidazoles were co-crystallized with fifteen halogen-bond donors. It was found that halogen bonds prefer best the acceptor site, demonstrating that a suitably activated halogen-bond donor can compete with a strong hydrogen-bond donor. The benefits of ‘double activation’ for promoting halogen bond effectiveness was explored with nine haloethynylnitrobenzenes. The positive potential on halogen atoms was enhanced through a combination of an sp-hybridized carbon and electron-withdrawing nitro group(s). Iodoethynylnitrobenzenes were identified as the most effective halogen-bond donors reported to date and the compounds were exploited for the interaction preferences of nitro group and nitro⋯X-Csp interactions were identified as synthetic tools for energetic co-crystal assembly. A synthetic strategy for the deliberate assembly of molecular polygons was developed utilizing bifurcated halogen bonds constructed from N-oxides and complementary halogen-bond donors via co-crystallization. A convenient, effective, and scalable protocol for stabilizing volatile liquid chemicals with co-crystallization was achieved. Through the use of halogen-bonding, liquid iodoperfluoroalkanes were transformed into crystalline materials with low-vapor pressure, considerable thermal stability and moisture resistance. To stabilize the energetic compound ethylenedinitramine, a co-crystallization approach targeting the acidic protons was employed. Eight co-crystals were obtained and the acceptors were identified as supramolecular protecting groups leading to diminished reactivity and enhanced stability while retaining the desirable energetic properties.
Keywords: Co-crystal; Halogen bond; Hydrogen bond; Crystal engineering; Supramolecular chemistry; Energetic co-crystal; Materials Science (0794); Molecular chemistry (0431); Organic Chemistry (0490)